The feasibility of interlibrary cooperation among the schools and colleges of nursing in Manila and Quezon City - Tobias, Loreto Paulite; Hidalgo, Namnama P.; Agayan, Crecencia C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1978)
The purpose of this study is to determine the feasibility of interlibrary cooperation among the schools and colleges of nursing in Manila and Quezon City. To determine the feasibility, various factors such as geographical, physical, economic, psychological and technological factors affecting the conditions and status of the respondents were studied.
A survey questionnaire was distributed among the chief librarians of the schools and colleges of nursing in manila and Quezon City. Data gathered through the questionnaire were supplemented by other data gathered from personal interviews and actual observation of library facilities.
Some of the conditions which tend to promote interlibrary cooperation exist among the respondent libraries. These are: 1. The libraries are linked by a common geography and by easily available transportation and communication.2. The libraries are homogeneous, serving common academic programs and common information needs.3. The libraries have scanty resources and stand to profit from even the most rudimentary sharing of sharing.4. The majority of the librarians are willing to participate in interlibrary loan mainly because their clienteles independently seek the services of neighboring facilities to satisfy information or book needs which cannot be fully satisfied in their proper institution. The feasible forms of interlibrary cooperation are interlibrary loan, bibliographic production, shared or cooperative cataloging, maintenance of a union catalog of holdings, cooperative indexing and cooperative acquisition.
Some of the barriers of interlibrary cooperative projects are the following: 1. Limited resources of most of the libraries in terms of staff, books, funds and reading room space. 2. Administrative and bureaucratic red tape from within and without the library. 3. Lack of financial resources, and4. Reluctance of larger libraries to lend a helping hand to poorer libraries.
In view of these problems, it is recommended that: 1. The schools and colleges of nursing libraries immediately undertake an expanded program of interlibrary lending among themselves informally or preferably on a formal basis. The four libraries which are already at present engaged in interlibrary lending should spearhead a drive to enlist the cooperation of the other nursing educational libraries in the lending and borrowing of materials.2. The cooperation of the two biggest nursing college libraries in Manila and Quezon City should be sought by the smaller libraries for the purpose of initiating work on a union catalog of holding and shared cataloging without which interlibrary loan cannot prosper much. The cooperation of these two libraries in interlibrary loan needed not be urged at the onset because it is not readily given and because it is not necessary for union cataloging work. It is, however, hoped that a history of cooperation in other activities will eventually induce full participation in the sharing and lending of resources.3. Whether interlibrary loan and other cooperative activities are established on informal or formal lines, the necessity exists for rules, regulations and policies conducive to flexible application and to interlibrary and adopted individually by the nursing libraries concerned.4. A professional forum for discussion and joint action under the aegis of a professional association may contribute much to the attainment of professional objectives. Such an association, or a chapter of an already existing professional organization may be organized.5. Nursing educational authorities should, in the pursuit of professional standardization, provide proper consortia or other avenues for cooperative acquisition and other forms of interlibrary cooperation, and provide or seek support for such activities.
Typescript.
Special Problem (Master of Library Science)
Keywords: Library cooperation -- Philippines; Nursing school libraries